The Effect of the Marketing Mix of MSME Products on Sales Volume During the Covid-19 Pandemic - murdayani, murdayani; Nurbaiti, Beti; Soehardi, Soehardi (Journal of Strategic and Global Studies, 2021)
This study aims to find out how much influence the marketing mix strategy has on sales volume during the Covid-19 pandemic on culinary MSMEs located in the North Bekasi area. The population is all culinary MSMEs in the North Bekasi area amounting to 1060 actors and sampling methods in the cluster sampling area of North Bekasi amounted to 104 MSMEs. The author uses quantitative methods using SEM (Structural Equation Modeling) and data analysis used with the Lisrel 8.70 software program. For primary data obtained through likert scale with validity, reliability and GOFI test. From the results of the study obtained the conclusion that the quality of products, prices and location has no effect on sales volume, only promotional variables that positively affect the sales volume of culinary MSMEs with micro criteria in North Bekasi